IMPLEMENTASI RESTRUKTURISASI PEMBIAYAAN MURABAHAH DI MASA PANDEMI COVID-19PADA BANK BJB SYARIAH KCP BOGOR - Riesha Mawarni Baity (2021)
The purpose of this study was to determine the implementation of murabaha financing restructuring at Bank BJB Syariah Bogor Branch and the implementation of financing restructuring based on POJK Number 48/POJK.03/2020 and DSN MUI Fatwa Number 47,47,49/DSN -MUI/II/2005 at Bank BJB Syariah Bogor Branch. This study uses qualitative research with a case study approach using data collection techniques through observation, interviews with three informants, and documentation of related parties from the Bank BJB Syariah Bogor branch. The results showed that the practice of restructuring murabaha financing at Bank BJB Syariah KCP Bogor was carried out as an effort to save non-performing financing. The implementation of restructuring when viewed from POJK, especially POJK 48 shows several important points that must be considered by banks. Bank BJB Syariah KCP Bogor, has guidelines for determining debtors affected by COVID-19. In addition, the implementation of the restructuring takes into account the DSN MUI Fatwa No. 47,48,49, regarding the settlement of problematic murabaha financing, the absence of additional costs, and the conversion of the contract.